BOSHQARUV TIZIMIDA RAHBARLIK VA LIDERLIK MOHIYATINING PSIXOLOGIYA SOHASI TADQIQOTLARIDA OʻRGANILGANLIK HOLATI - Elmurodov, U.Y. (SCIENCE and SOCIETY, 2022)
This article analyzes the work done in the system of leadership and management, the theoretical and practical aspects of management problems are analysed in the new era of management psychology.